Performative turn in postdramatic theatre - Piotr Grzymisławski (Przestrzenie Teorii)
In this article I try to identify changes that occur in the communication process in the theatre, which I call acceptance process. The core of perception in dramatic theatre up to now was the denial (term proposed by Anne Ubersfeld), which allows to participate in theatrical work. In theatre which leaves dramatic form, so-called postdramatic theatre, there is an acceptance process. This new situation in the theatre, by turning towards enforcing performative functions in the communication theatre, leads to changes in the relationship between stage and audience, their mutual temporary and spatial arrangement. In the contemporary art, not only in theatre, Auditorium turns into an Autorium – watching works becomes literally a creative activity, within which there are as many performances as many persons participating in an event – or as many images in each of performative entity’s mind.